2023
DOI: 10.1002/anie.202218039
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of CO2 on Au(310)@Cu High‐index Facets

Abstract: The chemical selectivity and faradaic efficiency of high‐index Cu facets for the CO2 reduction reaction (CO2RR) is investigated. More specifically, shape‐controlled nanoparticles enclosed by Cu {hk0} facets are fabricated using Cu multilayer deposition at three distinct layer thicknesses on the surface facets of Au truncated ditetragonal nanoprisms (Au DTPs). Au DTPs are shapes enclosed by 12 high‐index {310} facets. Facet angle analysis confirms DTP geometry. Elemental mapping analysis shows Cu surface layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…[76] It is demonstrated that the exposure of Cu high-index facets and a thicker (7 nm) Cu layer favored the formation and hydrogenation of *CO, which in turn promoted CH 4 production. [76] In summary, precise optimization of the catalytic performance is mainly achieved by modulating the catalytic crystalline facets and active site exposure.…”
Section: Electrocatalystmentioning
confidence: 98%
See 1 more Smart Citation
“…[76] It is demonstrated that the exposure of Cu high-index facets and a thicker (7 nm) Cu layer favored the formation and hydrogenation of *CO, which in turn promoted CH 4 production. [76] In summary, precise optimization of the catalytic performance is mainly achieved by modulating the catalytic crystalline facets and active site exposure.…”
Section: Electrocatalystmentioning
confidence: 98%
“…[72] Furthermore, the adsorption edge position of samples compared with Cu foil and CuO foil, which was obtained from XANES (Figure 3b), inferred the valence state of Cu. [43,72] The morphological and structural dependence in electrocatalytic CO 2 methanation, such as the external shape, [74] surface feature, [75] and crystalline structure [76] of the electrocatalysts, has been proved. For example, nanosheets were reported to provide direct channels for electron and proton transfer, facilitating charge transfer and mass transfer, optimizing active sites, and thus improving catalytic activity.…”
Section: Electrocatalystmentioning
confidence: 99%
“…Moreover, surface vacancies construct a rough surface that contain abundant dangling bonds and active valence electrons, resembling the high-index crystal facets. , For example, Wang et al reported quasi-spherical Cu 2 O with a rough surface and O vacancies (Cu 2 O/ILGS-400) (Figure b), instead of block shape with low-index exposed facets. In this configuration, the oxidation states were intermediate between Cu foil and Cu 2 O, facilitating the coverage and adsorption of CO to form C–C bonds.…”
Section: Strategies To Design Electronic Structure Of Tmcs In Co2rrmentioning
confidence: 99%
“…[ 62 ] Liang Liang et al found that Au‐truncated tetragonal nanoprisms (Au DTPs) enclosed by 12 high‐index facets‐supported Cu surface yielded a CH 4 /CO ratio of 10:1 compared with a ratio of 1:1 for 7 nm Au@Cu nanoparticles (NPs). [ 63 ] Tang et al demonstrated that entangled Cu nanowires with hierarchical pores in the presence of I − exhibited a C 2 FE of 80%, and the enhanced CRR activities could be derived from CO intermediate enrichment inside the hierarchical pores. [ 64 ] Hui Li et al created a Cu nanocrystal with a highly exposed facet ratio of (100)/(111) via facet‐selective atomic layer deposition technique to selectively cover the (111) surface of Cu with ultrathin Al 2 O 3 , resulting in a 22 times enhanced FE ratio of C 2 H 4 /CH 4 and a maximum FE of 60.4% for C 2 H 4.…”
Section: Monometallic Cu‐based Electrocatalysts For Crrmentioning
confidence: 99%